Why is perceived entrapment able to predict suicidal ideation? - Zempoalteca-Buenavista, Citlalli; Reyes-Garnica, Alfonso; Ortiz, Mario Isidoro; Ordóñez-Velázquez, Isi Iris (Journal of Basic and Applied Psychology Research, 2026)
Suicidal behaviour represents a care challenge for frontline healthcare personnel, as it requires having the skills and abilities to manage it—from the early identification of risk factors that condition the later emergence of suicidal ideation, to addressing psychiatric emergencies such as suicide attempts. The objective is to put into perspective the neurobiological background of suicidal ideation in order to understand the origin of this behaviour and to propose that the characteristics of entrapment make it behaviour susceptible to change, thus making it a key point for preventing subsequent suicidal behaviours. A literature review was conducted, first on the psychological theories that frame suicidal ideation, revealing that the Integrated Motivational-Volitional Model conceptualizes entrapment. Subsequently, research was conducted on published studies regarding the pathophysiological processes of suicidal behaviour. It was identified that entrapment is the neurocognitive process that proceeds the generation of suicidal thoughts. An individual experiencing adverse events perceives themselves as unable to escape these situations and therefore conceives the idea of dying as a way out. However, these thoughts are not present throughout the entire day, as shown by self-monitoring questionnaires and real-time imaging studies. Entrapment is behaviour susceptible to change and may help in preventing suicide risk.